Compact chelator-free Ni-integrated CuS nanoparticles with tunable near-infrared absorption and enhanced relaxivity for in vivo dual-modal photoacoustic/MR imaging. Issue 42 (12th October 2015) - Gao, Duyang; Zhang, Pengfei; Liu, Chengbo; Chen, Chi; Gao, Guanhui; Wu, Yayun; Sheng, Zonghai; Song, Liang; Cai, Lintao
Abstract : A novel PA/MRI dual-modal imaging nanoprobe with tunable NIR absorption and enhanced T 1 relaxivity was prepared via chelator-free method. Abstract : A chelator-free doping method is developed for constructing a Ni-integrated CuS nanostructure as a novel PA/MRI contrast agent. It exhibits tunable near-infrared absorption. Moreover, the hybrid nanostructure has demonstrated a dramatically enhanced T 1 relaxivity compared with Ni ions. Due to these unique properties, chelator-free nanoparticles have been successfully applied for in vivo PA/MRI dual-modal imaging.